Using Financial Market Information to Enhance Canadian Fiscal Policy - Huw Lloyd-Ellis; Xiaodong Zhu (Queen's University, Department of Economics, 2004)
In this article we argue that the evaluation and implementation of Canadian fiscal policy could be significantly improved through the systematic use of information provided by global financial markets. In particular, we show how the information contained in internationally traded asset returns can be used to (1) provide a more meaningful cyclical-adjustment of the budget deficit, (2) assess the sustainability of the public debt, and (3) reduce the risk of the debt becoming unsustainable without having to run excessively large surpluses.
Keywords: G1; H6; 330; Public debt; cyclically-adjusted deficit; sustainability; hedging; Finanzmarkt; Informationsökonomik; Konjunkturtheorie; Finanzpolitik; Haushaltsplanung; Kanada